2019
DOI: 10.1111/1745-9125.12206
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining Sutherland 80 years after white‐collar crime*

Abstract: Eighty years ago, Edwin H. Sutherland conceptualized and defined white‐collar crime. In this article, I engage retrospectively with Sutherland's ideas and work to emphasize important aspects that continue to guide research today; to note where he was prescient as well as shortsighted. I center this discussion around “corporate crime” or crimes by business. Four main themes are discussed: 1) law and official responses to corporate offending—the data problem, 2) corporate crime and the life cycle of organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 80 publications
1
24
0
Order By: Relevance
“…Nevertheless, unlike street crimes the criminal sanction plays a small role in the overall sanctioning of white-collar crimes (M. J. Lynch et al, 2016;Simpson, 2019). Rather than responding with calls for more criminal indictments, fines and prison terms for corporate executives, some legal scholars have argued that the street crimes should be handled more like white-collar crimes, with a variety of deterrence options (Schell-Busey et al, 2016), and that smart policing shown to be effective with street crime could be scaled to address corporate crimes (Brown, 2001;Laufer, 2017).…”
Section: Cecsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, unlike street crimes the criminal sanction plays a small role in the overall sanctioning of white-collar crimes (M. J. Lynch et al, 2016;Simpson, 2019). Rather than responding with calls for more criminal indictments, fines and prison terms for corporate executives, some legal scholars have argued that the street crimes should be handled more like white-collar crimes, with a variety of deterrence options (Schell-Busey et al, 2016), and that smart policing shown to be effective with street crime could be scaled to address corporate crimes (Brown, 2001;Laufer, 2017).…”
Section: Cecsmentioning
confidence: 99%
“…Second, because the dataset is based on criminal complaints, there is no information on firms sanctioned by the EPA under administrative and civil statutes. As others have noted, criminal referrals by the EPA to the DOJ are relatively infrequent and appear to be on the decline over the last few years (Kates, 2014; Simpson, 2019). On the other hand, what the EFD and similar datasets constructed from archival documents allow is the employment of mixed methods.…”
Section: Two Approaches To Building a Cec Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…Simpson (2019), Alvesalo-Kuusi and Whyte (2018), Geis (2015), Teachout (2014), and Yeager (2009) have delivered recent state-of-the-art reflections and assessments. These same criminologists have also provided historical frameworks for the developing areas of white collar and corporate crime inquiry.…”
mentioning
confidence: 99%